Êthos y Eudaimonía en la Ethika de Aristóteles - Anaya, John Didier (2011)
The focus of Aristotelian ethics is not to understand the essence of virtue, but rather the formation of underlying principles which define each individual’s ethics (êthos) that promotes happiness (eudaimonía) as their ultimate end. In this article I will emphasize the relationship between eudaimonía and ethos. This is relevant because êthos may be interpreted as source (pegé) from decisions as character or imprint, (charaktér) thanks to actions performed in order to reach eudaimonía.